Transfer of Organochlorine Pesticide Residues during Household and Industrial Processing of Ginseng - Peiling Wu; Mengying Gu; Yujie Wang; Jian Xue; Xiaoli Wu (Journal of Food Quality)
Ginseng is an important traditional herbal medicine; however, ginseng root may contain pesticide residues that may cause adverse health effects to consumers. Generally, people are more inclined to take the household- or industrial-processed ginseng products, instead of eating them directly. To investigate the intake of pesticides along with ginseng more specifically, we simulated two household processing methods (boiling and brewing) and two industrial processing methods (ethanol refluxing and boiling combined with resin purification) and then calculated the transfer rates of five organochlorine pesticide (OCP) residues in ginseng. The determination of targeted pesticide residues in ginseng was done by gas chromatography-electron capture detector (GC-ECD), and the confirmation was done by gas chromatography-tandem mass spectrometer (GC-MS/MS). The transfer rates of five OCPs during boiling, brewing, ethanol refluxing, and boiling combined with resin purification were 3.44%–34.43%, 1.47%–38.12%, 34.81%–57.0%, and 0–2.91%, respectively. The transfer rates of the OCPs in water extraction (boiling and brewing) were relatively low and would not increase significantly along with two hours of boiling. The OCPs were concentrated during the ethanol refluxing procedure because of the high transfer rates of the OCPs and the reduction of the weight of products. The boiling combined with resin purification method removed the OCPs most effectively. Different ginseng processing methods resulted in variable transfer rates of pesticides, as well as a diverse exposure risk of pesticides to humans. Consequently, it is necessary to concern about the transfer rates of pesticide residues during ginseng processing.